Censorship of Anime in Italian Distribution - Parini, Ilaria (Meta, 2012)
Editing of anime – Japanese cartoons – is a process through which the product is altered in order to make it appropriate for the public. Such a practice is quite common all over the Western world, and Italy is no exception. Japanese anime are not designed only for an audience of children, and there exist different types of products aimed at viewers of different ages; consequently, in Japan anime are shown at various time slots according to their characteristics. In Italy, on the contrary, cartoons are generally considered a product targeted exclusively at children, and even those anime which were originally designed for an older audience are broadcast during the protected time slot and therefore have to comply to certain standards regarding their content and the type of language spoken. Censorship thus tends to take place both on the visual and the verbal levels: scenes considered inappropriate are removed from the story, the plot is often changed, the text is frequently domesticated in its references to the Japanese culture, and the language is flattened. Italian translators take an active part in the editing of anime: as they are the first ones to actually see the episodes, they are supposed to report to their commissioners any ambiguous element they come across, and they perform (self)censorship on the verbal level, manipulating the dialogue exchanges as is expected by the translation company.